Bridging Legal Traditions in Consumer Protection: Criminal Liability in Comparative Jurisprudence and Contemporary Islamic Law - Bambang Suheryadi; Hariyanto; Bambang Sugeng Ariadi Subagyono; Agus Yudha Hernoko; HD. Djunaedi (MILRev: Metro Islamic Law Review, 2026)
Consumer protection has become an increasingly urgent legal issue in the era of global trade and digital commerce, where complex market structures and cross-border transactions intensify the vulnerability of consumers. This study aims to examine the construction of criminal liability in consumer protection by bridging different legal traditions through a comparative analysis of contemporary legal systems and Islamic legal principles. The research employs a normative legal method, using a comparative and conceptual approach to analyse statutory regulations, jurisprudence, and legal scholarship from several jurisdictions, including Indonesia, the United Kingdom, and Malaysia, alongside perspectives from contemporary Islamic law. The findings demonstrate that Indonesia's consumer protection regime, regulated under Law No. 8 of 1999 on Consumer Protection, is primarily grounded in the principles of benefit, justice, and legal certainty. Yet, it still places criminal sanctions as ultimum remedium and largely relies on fault-based liability with a reverse burden of proof. In contrast, the United Kingdom applies a strict liability regime for defective products, influenced by the Product Liability Directive, which enables stronger producer accountability regardless of fault. Malaysia adopts a hybrid regulatory approach, particularly in addressing consumer risks within digital and online transactions. From the perspective of contemporary Islamic law, consumer protection is normatively supported by principles such as the protection of property (ḥifẓ al-māl), the removal of harm (al-ḍarar yuzāl), and the prohibition of fraudulent practices (gharar and tadlīs), which conceptually reinforce stricter liability frameworks for producers. This study contributes to the development of consumer protection discourse by proposing a bridging framework between comparative jurisprudence and Islamic legal principles. It argues that integrating strict liability concepts with maqāṣid-oriented Islamic legal values can strengthen the normative and institutional design of consumer protection regimes, particularly in Indonesia, by enhancing legal certainty, accountability, and consumer justice in the contemporary marketplace.